Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social group size influences pathogen transmission in salamanders - Kendra L. Ritchie; Vance T. Vredenburg; Shruti Chaukulkar; Helen M. Butler; Andrew G. Zink (Behavioral Ecology and Sociobiology, 2021)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Landscape and climate determine patterns of spread for all colour morphs of the alien ladybird Harmonia axyridis - Bethan V. Purse; Richard Comont; Adam Butler; Peter M. J. Brown; Clare Kessel; Helen E. Roy (Journal of Biogeography, 2015)
Aim Understanding why some areas are more vulnerable to invasion by invasive alien species than others represents a key challenge in invasion biology. We investigated the roles of landscape, climate, proximity to initial invasion sites, recording intensity and colour pattern polymorphism in explaining the spread of the invasive ladybird Harmonia axyridis across Great Britain. Location The British mainland and inshore islands (Anglesey, Isle of Wight and the Inner Hebrides). Methods Patterns in time to invasion of H. axyridis were quantified at a hectad level (10 km grid squares) from over 23,000 records. Bayesian spatial survival models were developed relating spread patterns to concurrent patterns in climate, land cover and recording intensity. Separate models were developed for melanic (f. conspicua and f. spectabilis ) and non‐melanic (f. succinea ) colour forms that were hypothesized to differ in their response to climate factors, particularly temperature, and subsequent spread. Results Harmonia axyridis spread more rapidly into hectads containing a high proportion of urban land cover and marginally more slowly into hectads containing high conifer cover. Invasions were recorded more rapidly in hectads with high recording intensity, or that were close to initial invasion sites. Harmonia axyridis colour morphs spread to similar extents, although increased sunshine significantly enhanced the spread of the non‐melanic form (f. succinea ). Correspondence between observed and predicted times of invasion from survival models was substantial (Pearson's r p for all H. axyridis colour forms = 0.834). Main conclusions The ability of H. axyridis to use a wide range of habitats and prey species and overwinter inside buildings may have allowed this species to establish rapidly in urban areas. Native ladybird species in urban areas may suffer combined negative impacts of habitat deterioration and competition from H. axyridis . Spatial survival models help us to identify areas vulnerable to invasion and to understand the impacts of multiple environmental drivers on the spread of invasive alien species, given detailed data on time to invasion.

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)